A Multilayer PDMS Microfluidic with High Optical Transmission for DNA Detection - Masrie, Marianah; Yunas, Jumril; Yeop Majlis, Burhanuddin (Micro and Nanosystems, 2015)
This paper presents deoxyribonucleic acid (DNA) detection in an optical system by utilizing a multilayer polydimethylsiloxane (PDMS) microfluidic chamber through ultraviolet (UV) absorption process. Nucleic acids have high absorption in the UV range between 240 to 275 nm, and this property adapts to this work since DNA induces a significant absorbance change specifically at 260 nm. The multilayer PDMS microfluidic was produced by a spin coat process on the SU-8 mold. An optical system was developed to measure the change in light intensity over 500 μs, and the absorbance of the DNA samples were derived. The optical transmission properties of various samples with different thicknesses of PDMS are also investigated under UV light illumination. This characterization is to prove that the multilayer PDMS microfluidic is suitable as the device for DNA detection since the thickness is less than 1000 μm and having a higher percentage of the optical transmission. In DNA detection, significant experimental results were achieved, with the absorbance coefficient averaged between 0.07 and 0.09 a.u.
Keywords: optical system